(3RHOI GdWHs - (3ESeGYjd Hf MSjf GdMSjfj, CHh EHQGgje, Rjf GdOjf GdLQLGfj,J (B531 (3g` s ((3eMehO Hf YeQ Hf eMehO GdMSjfi s)
(3ChdgG (B:s
(3CeG HYO MeOkG ddg SHMGfg hGdKfG Ydjg aGYde Gf eHfi GdWH Ydi eYQaI MGdJi HOf GdGfSGf ef GdUMI hGdeQV GdebGdI GdChdi ai GdfHV s
(3BNQgG (B:s
(3Ke cJGH GdSehe hJe HJeGeg cJGH GdRHOI ai GdWH hGdMeO ddg hMOg s
(3cJHJ Ghdi hQbI HNW QbYIs
(3Gced GdeNWhW HNW fSN HChdgG ebOeI Ke agQSJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B308s
Keywords: (3GdWHs